Dropping Out of School: Explaining How Concerns for the Family’s Social-Image and Self-Image Predict Anger - Gausel, Nicolay; Bourguignon, David (Frontiers in Psychology, 2020)
As dropping out of school is considered a violation of moral norms, the family associated with the drop out can react with anger directed towards the pupil or with anger directed at others that might know of the drop out. In our vignette study (N = 129), we found that anger at others and anger at the pupil was significantly higher if our community participants imagined a drop-out from a vocational education rather than a general education. As expected, anger directed at others was fully explained by a concern for the family’s social-image (i.e., a concern for condemnation by others), while anger directed at the former pupil was fully explained by a concern for the family’s self-image (i.e., a concern for their moral self-image). Thoughts for how to better understand family reactions in relation to drop out are discussed.